When Deciding to Translate Means Risking Your Reputation: How an American Translator Became a “Spy,” and a Chinese Author, an “Enemy from America” - Tian, Ye (TTR, 2022)
While research on the role of translation in society largely focuses on the reception of translated texts, this article calls for a closer look at the decision to translate. It proposes that, on a micro-level, the decision to translate, in the context of an ideological and political conflict, has the potential to subvert the image of authors and translators as perceived by certain groups of people. It reveals how opinions regarding translators and authors are often a product of ideological stances rather than widespread reading of either the authored text or its translation. In this case, it is not a collective reading of the translation itself that sways the perception but, rather, a political “reading” of the translator’s and author’s respective images, which consequently influences their reputation within these groups. This article investigates the translation of a “diary” that recorded events during the Wuhan lockdown (January-April 2020) and garnered much attention on Weibo, China’s largest social media platform. Comments shared on Weibo about the author, Wang Fang, also known as Fang Fang, and the American translator, Michael Berry, were significantly different before and after the publication of Berry’s translation, intitled WuhanDiary. By examining a sample of Weibo users’ reactions, the article seeks to understand the rationale behind the changing perceptions of the author’s and the translator’s image. It argues that Berry, through his decision to translate, comes to be perceived by Weibo users as a “spy,” while Fang Fang, having given her consent for her “diary” to be translated, is then perceived as an “enemy from America.” Translation is thus seen to play a significant role in subverting both an author’s and a translator’s reputation at the micro-level.